Automatic generation control for microgrids - Tan, Yean Sang. (2011)
A microgrid can operate either as an isolated power system or a grid-connected system. Automatic Generation Control (AGC) is needed to provide supplementary control to the power system to maintain the system frequency. Load Frequency Control is performed using frequency deviation method via proportion-integral control. When the microgrid operates as an isolated power system, cost minimization is required to reduce the operating costs of the power system. When the microgrid is connected to main grid, generation should be done in such a way that the profit of the microgrid is maximized. In this project, the proposed Matrix Method and Graphical Method are discussed and implemented. The complexity, the efficiency and viability of these methods are compared thoroughly to ensure the maximum profits of the microgrid system can be realized.